Non-rigid motion-corrected free-breathing 3D myocardial Dixon LGE imaging in a clinical setting - Zeilinger, Martin; Kunze, Karl Philipp; Munoz, Camila; Neji, Radhouene; Schmidt, Michaela; Croisille, Pierre; Heiß, Rafael; Wuest, Wolfgang; Uder, Michael; Botnar, René Michael; Treutlein, Christoph; Prieto, Claudia (European Radiology, 2022)
Objectives: To investigate the efficacy of an in-line non-rigid motion-compensated reconstruction (NRC) in an image-navigated high-resolution three-dimensional late gadolinium enhancement (LGE) sequence with Dixon water–fat separation, in a clinical setting. Methods: Forty-seven consecutive patients were enrolled prospectively and examined with 1.5 T MRI. NRC reconstructions were compared to translational motion-compensated reconstructions (TC) of the same datasets in overall and different sub-category image quality scores, diagnostic confidence, contrast ratios, LGE pattern, and semiautomatic LGE quantification. Results: NRC outperformed TC in all image quality scores (p < 0.001 to 0.016; e.g., overall image quality 5/5 points vs. 4/5). Overall image quality was downgraded in only 23% of NRC datasets vs. 53% of TC datasets due to residual respiratory motion. In both reconstructions, LGE was rated as ischemic in 11 patients and non-ischemic in 10 patients, while it was absent in 26 patients. NRC delivered significantly higher LGE-to-myocardium and blood-to-myocardium contrast ratios (median 6.33 vs. 5.96, p < 0.001 and 4.88 vs. 4.66, p < 0.001, respectively). Automatically detected LGE mass was significantly lower in the NRC reconstruction (p < 0.001). Diagnostic confidence was identical in all cases, with high confidence in 89% and probable in 11% datasets for both reconstructions. No case was rated as inconclusive. Conclusions: The in-line implementation of a non-rigid motion-compensated reconstruction framework improved image quality in image-navigated free-breathing, isotropic high-resolution 3D LGE imaging with undersampled spiral-like Cartesian sampling and Dixon water–fat separation compared to translational motion correction of the same datasets. The sharper depictions of LGE may lead to more accurate measures of LGE mass. Key Points: • 3D LGE imaging provides high-resolution detection of myocardial scarring. • Non-rigid motion correction provides better image quality in cardiac MRI. • Non-rigid motion correction may lead to more accurate measures of LGE mass.
CRIS-Team Scopus Importer:2022-02-25
Keywords: Heart; Magnetic resonance imaging; Myocardium; Three-dimensional imaging